2019
DOI: 10.21273/hortsci13874-19
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Tomato Rootstock on Hybrid and Heirloom Tomato Performance in a Midwest High Tunnel Production System

Abstract: High tunnels allow vegetable growers to extend the growing season, increase crop production, and improve produce quality. Tomatoes (Solanum lycopersicum L.) are the most widely grown crops in high tunnels; however, tomato production in high tunnels can be challenging. Continuous cropping in high tunnels can increase soil-borne disease pressure and can lead to soil salinity or nutrient depletion issues. Based on preliminary research, we hypothesized that use of the rootstock 'RST-04-106-T' would increase yield … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 39 publications
5
22
0
Order By: Relevance
“…However, Pearson correlation analysis revealed a lack of correlation between the lycopene content of disease-resistant and WT rootstocks for all three tomato varieties. This observation corresponds to previous studies that have shown that the lycopene content remained unchanged [ 33 , 43 ]. However, others have reported a decrease in lycopene content as a result of grafting [ 45 , 55 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…However, Pearson correlation analysis revealed a lack of correlation between the lycopene content of disease-resistant and WT rootstocks for all three tomato varieties. This observation corresponds to previous studies that have shown that the lycopene content remained unchanged [ 33 , 43 ]. However, others have reported a decrease in lycopene content as a result of grafting [ 45 , 55 ].…”
Section: Discussionsupporting
confidence: 92%
“…Studies have shown that tomatoes contain many types of antioxidants, including lycopene, flavonoids, and hydroxycinnamic acids, as well as other phenols [ 48 , 49 , 50 ]. However, while heirloom tomatoes are popular among consumers, the varieties are often challenging to produce due to disease susceptibility and low yield [ 30 , 32 , 33 , 34 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PLANT MATERIAL, GRAFTING, AND HEALING. 'Cherokee Purple' (Johnny's Selected Seeds, Winslow, ME) was selected as the scion because it represents an heirloom tomato that is commonly used by small-scale growers (Lang and Nair, 2019). 'RST-04-106-T' (DP Seeds, Yuma, AZ), was selected as the rootstock because it had been used in prior research in combination with 'Cherokee Purple' (Lang and Nair, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…2017) when the stem diameters were appropriate for splice grafting. Tomatoes were grafted using the splice grafting method (Lee et al, 2010), as previously outlined by Lang and Nair (2019). Grafting was completed within 4.5 and 3.5 h for repetitions 1 and 2, respectively.…”
Section: Methodsmentioning
confidence: 99%